Ungulate saliva inhibits a grass–endophyte mutualism - Tanentzap, Andrew J. (The Royal Society, 2014)
Fungal endophytes modify plant–herbivore interactions by producing toxic alkaloids that deter herbivory. However, studies have neglected the direct effects herbivores may have on endophytes. Antifungal properties and signalling effectors in herbivore saliva suggest that evolutionary pressures may select for animals that mitigate the effects of endophyte-produced alkaloids. Here, we tested whether saliva of moose (Alces alces) and European reindeer (Rangifer tarandus) reduced hyphal elongation and production of ergot alkaloids by the foliar endophyte Epichloë festucae associated with the globally distributed red fescue Festuca rubra. Both moose and reindeer saliva reduced the growth of isolated endophyte hyphae when compared with a treatment of distilled water. Induction of the highly toxic alkaloid ergovaline was also inhibited in plants from the core of F. rubra's distribution when treated with moose saliva following simulated grazing. In genotypes from the southern limit of the species' distribution, ergovaline was constitutively expressed, as predicted where growth is environmentally limited. Our results now present the first evidence, to our knowledge, that ungulate saliva can combat plant defences produced by a grass–endophyte mutualism.